Notes on the Attributed Powers of International Organizations - Gadkowski, Andrzej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
This article aims to explore the fundamental aspects of the the concept of attributed powers of international organizations. This subject holds significant importance, as attributed powers are related to the very nature of international organizations and their international subjectivity. The author discusses the essence of the attributed powers of international organizations, the doctrinal assessment of this concept, and the selected decisions of international courts that have addressed this issue.